The Role of Hypothyroidism in Male Infertility and Erectile Dysfunction - Mohammad Reza Nikoobakht; Mehdi Aloosh; Nafiseh Nikoobakht; Abdolrasoul Mehrsai; Farzad Biniaz; Mohammad Amin Karjalian (Urology Journal, 2012)
Purpose: To evaluate the effect of hypothyroidism on erectile function and sperm parameters. Materials and Methods: This study was conducted on 24 patients with hypothyroidism and 66 normal individuals. Serum levels of hormones, including thyroid stimulating hormone (TSH), thyroxin (T4), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and testosterone, were measured and semen analysis was done in all the participants. Erectile function was evaluated using International Index of Erectile Function (IIEF-5) questionnaire. Results: The mean IIEF-5 total score was 11.75 [95% confidence interval (CI): 9.70 to 13.79) and 20.81 (95% CI: 20.02 to 21.6) for hypothyroid group and normal subjects, respectively (P = .005). Furthermore, serum concentrations of PRL and seminal parameters were significantly different between two groups (P < .001). Conclusion: Hypothyroidism adversely affects erectile function and sperm parameters, including sperm count, morphology, and motility. In patients with sperm abnormalities and erectile dysfunction, measurement of thyroid hormones is recommended.